Development of test device for strength and rheological properties of agricultural materials - WANG Jian-ping; TIAN Hong-ping; WANG Jun (浙江大学学报. 农业与生命科学版, 2002)
A test device for strength and rheological properties of agricultural materials was described. It could be used for testing of stress-strain, creep and stress-relaxation of agricultural materials. An automatic data acquisition and control system for the test device was developed. A displacement sensor, a load sensor, a high-performance DAS card and a digital I/O card were interfaced with a microcomputer for this purpose. Performance of the test device was demonstrated by using it in testing for firmness of peach and pear.